Who Am I and What Am I Doing Here? : Learning to Take Yourself and Your Experiences Seriously - Frog, Mr. (INSTITUTE FOR THE STUDY OF RELIGIONS, 2024)
Doing fieldwork is itself a learning process, and it can be a profoundly educational one, yet it can simultaneously be bewildering, terrifying, and the situation itself can produce an existential crisis. This modest essay talks about my own experiences with such issues. It is organized through a series of cases that include encounters with a ‘last singer’ of kalevalaic poetry in Finland, drum-dancers in East Greenland, a ram-sacrifice in the Republic of Karelia, and a perambulation into digital ethnography. Everyone’s experiences with fieldwork are unique, but these examples illustrate how your imagination of what ‘fieldwork’ is and who is qualified to do it can be a stumbling block that you unwittingly throw in front of yourself. A key point here is that anyone can do fieldwork, and, especially when you are just starting out, it is normal to feel stressed and uncertain, to blunder through situations and make mistakes. I set out my own experiences here with the hope that others can learn lessons from them more quickly than I did. The highlights of these lessons are quite basic: get permissions with full disclosure; take better notes; be aware of ethical issues; if you are there to learn from others, be prepared to find your way collaboratively; don’t underestimate the value of your experiences; and remember to breathe. Peer reviewed